Perbandingan Hukum Perlindungan Konsumen Terkait Jasa Titip Tiket di Indonesia dan Amerika Serikat - Ester Gloria Anastasia; Ratna Artha Windari; Ni Ketut Sari Adnyani (IAIN Langsa, 2026)
This study analyzes consumer legal protection in the practice of digital concert ticket concierge services in Indonesia based on the right to